Elastic Properties Modeling for Identification of Prospective Reservoir Zones in the Carbonate Reservoir, MRD Field in the North East Java Basin - Mordekhai Mordekhai; Sonny Winardhi (Himpunan Ahli Geofisika Indonesia (HAGI), 2019)
“MRD” field is an oil and gas field which located in Rembang Zone. One of the hydrocarbon zones in this fieldlies in Ngimbang Formation. Reservoir in this field has a lifespan of Middle Eocene to Early Oligocene. Reservoir of this formation is carbonate rocks and dominated by calcite and dolomite minerals. One of the uniqueness of this kind of reservoir is the pore shape which quite complex. In this study, reservoir characterization which performed on this field is based on elastic properties modelling. Elastic Properties modelling which was conducted in this field can provide an output of the pore shape, aspect ratio, and the fraction of each respective poresforms that exist in this field’s reservoir zone. Therefore the primary data such as petrophysical data, XRD (X-Ray Diffraction), and the data of other reservoir parameters are needed for more accurate resultsobtained with real conditions. The result of this modelling shows that the shape of the pores in the reservoir zone at any depth can be predicted. Distribution of pore shapes that exist in the two wells can be used as a reference for prospective determination of hydrocarbon zones in “MRD” field.